If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + an = 6x Reorder the terms: an + 3b = 6x Solving an + 3b = 6x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. an + 3b + -3b = -3b + 6x Combine like terms: 3b + -3b = 0 an + 0 = -3b + 6x an = -3b + 6x Divide each side by 'n'. a = -3bn-1 + 6n-1x Simplifying a = -3bn-1 + 6n-1x
| 7x-15=-106 | | -2x+32= | | -4=-2-x | | 4(5x+7)-3x=(4x-9) | | 5x+9+7x+7=2x+10x+13 | | 35q=q | | 3(x+2)-2y=0 | | 13x-33+10x=180 | | 5x^2+5y^2-xy-11x+11y+11=0 | | -7h+5=-44 | | -7+5=-44 | | 80=62+0.60x | | 6+k-4=11 | | 27x+4+3x+1=180 | | (4x-8)+4(4x-8)+12= | | 3x-2(6+7x)=-100 | | 3(x+3)=4(x-8) | | -5x+45= | | 2(3m-4)=10 | | h=563-503-083100t+4000 | | cp=4p+d | | 6xn=-30 | | -9x-72= | | 7x=2(y+5) | | -1m+9=7 | | Cos8x=(1/2) | | 15+m=-70 | | -9x-10+6x-1=9 | | .25-4=2z | | 32.4-5= | | -4x=-6y-10 | | 2/3*(x-3) |